Report for proposed new design for Aik Cheong Cafe at No. 2, Kuala Paya, 50500 Kuala Lumpur / Norlida Ramly - Ramly, Norlida (Faculty of Architecture, Planning and Surveying, 2009)
From all the research that had been done, every process of cafe design must take care of several things including project objectives, the feasibility study, technical requirements and the concept. In relation to this research, I had opportunity to observe the expansion of theme cafe where this type of cafe is getting more popular nowadays. Beside that, I also had discovered problems in cafe or coffee house business such as orientation of cafes must be suitable to give a good flow and some of cafes not using concept in its design beside they just decorate the cafe to look interesting such as put some photo frame or plants. Moreover, cafe also plays its own role in sending massage for example, the images and theme that is shown will give information and effect to customers.If we see now, most of customers not understand about the image and concept that want to be shown in every cafe design. This we can see that customers more interested in cafe that use international image and concept. For them, local theme such as Malay traditional and Baba & Nyonya are not interesting. It seems that international cafes set the trend that the locals have to follow. So, this Aik Cheong cafe presents a cafe that have images of traditional Malaysia elements with modem contemporary. This cafe will still have Eastern characteristic. This to ensure that the cafe can be accepted by all kind of people either tourists or local people.